High toughness light curing coating

By using high-toughness photocuring coating composed of polyunsaturated double bonds and polyphosphonic acid-based compounds, the problem of insufficient bonding and bending cracking resistance in new energy vehicle batteries is solved, and excellent shear strength and attachment are achieved Focus on improving bending resistance.

CN118222174BActive Publication Date: 2024-12-20GUANGZHOU WANWEI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410448743.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-15
Publication Date
2024-12-20
Estimated Expiration
2044-04-15

AI Technical Summary

Technical Problem

While ensuring insulation performance, existing photocuring coatings are difficult to meet the requirements of new energy vehicle batteries for high bonding and bending cracking resistance.

Method used

High-tough photocuring coatings composed of polyunsaturated double bonds and polyphosphonic acid-based compounds are used to improve the shear strength and adhesion of the coating and enhance the bending resistance through specific preparation methods and component ratios.

Benefits of technology

It significantly improves the shear strength, adhesion and bending resistance of photocured coatings, meeting the requirements of new energy vehicle batteries for bonding performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118222174B_ABST
    Figure CN118222174B_ABST
Patent Text Reader

Abstract

The present invention provides a high-toughness photocurable coating, which comprises the following components, measured in parts by weight: 60 to 85 parts of acrylate monomers; 8 to 25 parts of polyurethane acrylate resins; 2 to 8 parts of compound A; 1 to 5 parts of photoinitiator; 0.1 to 0.8 parts of wetting agent; 0.1 to 0.8 parts of defoaming agent; and 0.5 to 2 parts of pigment, which can meet the requirements of batteries for bonding performance, bending crack resistance and adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy vehicle batteries, and in particular relates to battery insulating materials, and specifically relates to high-toughness photocuring coatings. Background Art

[0002] New energy vehicles use unconventional automotive fuels as their power source, and have achieved unprecedented breakthroughs in terms of types, technology, and market share. New energy vehicles that use non-petroleum fuels usually use batteries as their energy storage power source.

[0003] In order to ensure good bonding and insulation properties of square shell batteries, some manufacturers currently use a photocuring coating solution. Compared with other photocuring coatings, the photocuring coating of the present invention has better bonding properties, bending crack resistance and adhesion while ensuring excellent insulation properties. Summary of the invention

[0004] The purpose of the present invention is to overcome at least one disadvantage of the above-mentioned prior art and to provide a photocurable coating that can meet the requirements of the battery for bonding performance.

[0005] In order to solve the above technical problems, the present invention provides a high-toughness photocurable coating, which comprises the following components in parts by weight:

[0006]

[0007] The preparation method of compound A comprises the following steps:

[0008] (1) Compound B is added to toluene, and after azeotropic dehydration under nitrogen, the mixture is cooled to 80°C to 100°C, chloroplatinic acid is added, and a mixture of compound C and toluene is added dropwise, and the mixture is stirred to react to obtain compound D; the azeotropic dehydration time is 1 to 3 hours, preferably 2 hours, the cooling temperature is preferably 90°C, and the dropwise addition time of compound C is preferably controlled within 2 hours; the stirring reaction temperature is 100°C to 110°C, preferably 105°C, and the stirring reaction time is 5 to 7 hours, preferably 6 hours;

[0009] Wherein, the structural formula of compound B is: The structural formula of compound C is: The structural formula of compound D is:

[0010] Where n = 10 to 30;

[0011] (2) Compound D is added to toluene, and concentrated sulfuric acid is added, the temperature is raised and acrylic acid is added. After the reaction is completed, the temperature is raised to 110° C. to 130° C., preferably 120° C., and the temperature is raised to 120° C. and kept warm for 10 minutes; the acrylic acid addition time is controlled to be 1 to 3 hours, preferably 2 hours; a cooling reflux device is used to collect the water generated during the reaction. After the acrylic acid is added, the reaction is continued until no water is generated, and the reaction is considered to be completed; intermediate E is obtained, the temperature is lowered to 100° C. to 120° C., preferably 110° C., and a mixed solution of dibenzoyl peroxide, vinylphosphonic acid and toluene is continued to be added to the reaction solution. The addition time is controlled to be 1 to 3 hours, preferably 2 hours. After the reaction, the reaction is continued at 110° C. for 1 hour, and toluene is distilled off under reduced pressure to obtain the compound A;

[0012] The structural formula of intermediate E is: Where n=10~30.

[0013] Preferably, the polyurethane acrylic resin is selected from one or both of aliphatic polyurethane acrylate resin and aromatic polyurethane acrylate resin, and the resin viscosity is: 10000-80000cps@60℃, elongation is 20-150%, and functionality is: 2-6. Preferably, the aliphatic polyurethane acrylate resin has a viscosity of 20000-60000cps@60℃, an elongation of 20-50%, and functionality: 2.

[0014] Preferably, the acrylic ester monomers include: 5 to 20 parts of a first acrylic ester monomer, 10 to 40 parts of a second acrylic ester monomer, 10 to 40 parts of a third acrylic ester monomer, 3 to 20 parts of a fourth acrylic ester monomer, and 3 to 10 parts of a fifth acrylic ester monomer;

[0015] The first acrylate monomer is selected from one or both of tricyclodecane dimethanol diacrylate (TCDDA) and ethoxylated trimethylolpropane trimethacrylate (TMP9EOTMA), preferably tricyclodecane dimethanol diacrylate (TCDDA);

[0016] The second acrylate monomer is selected from one or two of dicyclopentadiene acrylate (DCPA), cyclotrimethylolpropane formal acrylate (DTFA), isobornyl methacrylate (IBOMA) and isobornyl acrylate (IBOA), preferably dicyclopentadiene acrylate (DCPA);

[0017] The third acrylate monomer is selected from one or two of dicyclopentenyl ethoxylated acrylate (DCPEA), dicyclopentenyl ethoxylated methacrylate (DCPEA) and dicyclopentyl methacrylate (HDCPMA), preferably dicyclopentenyl ethoxylated acrylate (DCPEA);

[0018] The fourth acrylate monomer is selected from one or two of lauric acid acrylate (LA), stearic acid acrylate (SA), octadecyl acrylate (BEA), lauric acid methacrylate (LMA), and 2-ethylhexyl methacrylate, preferably lauric acid acrylate (LA);

[0019] The fifth acrylate monomer is selected from one or two of 1,6-hexanediol diacrylate (HDDA), ethoxylated 1,6-hexanediol diacrylate (HD2EODA), dipropylene glycol diacrylate (DPGDA), tripropylene glycol diacrylate (TPGDA), neopentyl glycol diacrylate (NPGDA), propoxylated neopentyl glycol diacrylate (NPG2PODA), ethylene glycol dimethacrylate (EGDMA), triethylene glycol dimethacrylate (3EGDMA) and diethylene glycol dimethacrylate (DEGDMA).

[0020] Preferably, the acrylate monomers are composed of tricyclodecane dimethanol diacrylate, dicyclopentadiene acrylate, dicyclopentenyl ethoxylated acrylate, lauric acid acrylate, and 1,6-hexanediol diacrylate.

[0021] Preferably, the photoinitiator is selected from α-cleavage type free radical photoinitiator or hydrogen elimination type free radical photoinitiator. Among them, the α-cleavage type free radical photoinitiator (Type I) is one or two of benzoin derivatives, benzyl ketal, α-α dialkyloxy acetophenone, α hydroxy alkyl phenone, α amino alkyl phenone and acyl phosphine oxide. Preferably, the photoinitiator is selected from acyl phosphine oxide.

[0022] Preferably, the wetting agent is a silicone wetting agent, and the defoaming agent is a foam-breaking polymer mixture that does not contain silicone.

[0023] Preferably, the pigment is ink blue. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the H-NMR spectrum of compound A.

[0025] Figure 2 is the H-NMR spectrum of compound D.

[0026] Figure 3 is the H-NMR spectrum of compound E. DETAILED DESCRIPTION

[0027] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0028] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.

[0029] The experimental methods in the following examples are conventional methods unless otherwise specified. The instruments and equipment used in the following examples are conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are purchased from conventional biochemical reagent stores unless otherwise specified.

[0030] The photocurable coating of the present invention uses a compound A having polyunsaturated double bonds and polyphosphonic acid groups. The polyunsaturated double bonds of the compound A enable the compound A to effectively participate in the photocuring reaction. After photocuring, the compound A and the main body are completely reacted and effectively combined together. The polyphosphonic acid group of the compound A can completely react with the metal substrate to ensure good shear strength. The polysilicon-oxygen structure of the compound A can achieve spatial rotation. Compared with currently known silane coupling agents such as vinyl silane and vinyl organic acids such as vinyl phosphonic acid, the photocurable coating is endowed with excellent toughness, thereby achieving excellent anti-bending performance.

[0031] The light-curing coating of the present invention significantly improves the anti-bending performance while meeting the shear strength and adhesion performance.

[0032] Example 1

[0033] Preparation of Compound A

[0034] (1) Preparation of Compound D

[0035] The structural formula is 100 g of compound B (commercial product, magnolol) was added to 400 g of toluene, and azeotropically dehydrated for 2 hours under nitrogen, then cooled to 90°C, 1.0 g of chloroplatinic acid was added, and 107 g of the structural formula was added dropwise over 2 hours. Compound C (commercially available, Si-H-containing dimethylsiloxane, n=10-30) was mixed with 428 g of toluene, and then stirred at 105°C for 6 hours to obtain a mixture of the formula

[0036] Compound D (n = 10 to 30), the hydrogen spectrum of compound D is as follows Figure 2 As shown;

[0037] (2) Preparation of Compound A

[0038] 0.2 mol of compound D was added to 600 g of toluene solution, and 15 g of concentrated sulfuric acid was added. The temperature was slowly raised to 120°C, and a stirring paddle was used to stir at a constant speed of 80 RPM. The temperature was raised to 120°C and kept warm for 10 minutes. Acrylic acid was slowly added, and a total amount of 0.8 mol of acrylic acid was slowly added over 2 hours. The water produced in the reaction was collected using a cooling reflux device. After the addition of acrylic acid was completed, the reaction was continued until no water was produced, and the reaction was considered to be completed. The product was mainly intermediate E, and its hydrogen spectrum was as follows: Figure 3 As shown, the structural formula is:

[0039] After the temperature was lowered to 110°C and stabilized for 10 minutes, 15 g of dibenzoyl peroxide, 1.2 mol of vinylphosphonic acid and 30 g of toluene were slowly added to the solution. The total time was controlled to be 2 hours. After the addition was completed, the reaction was continued at 110°C for one hour. Toluene was distilled off under reduced pressure to obtain compound A. The H-NMR spectrum of compound A is shown in Figure 1 shown.

[0040] Embodiment 2:

[0041] This embodiment 2 provides a high-toughness photocurable coating, which is composed of the following components in parts by weight:

[0042] 10 parts of tricyclodecane dimethanol diacrylate (TCDDA), 30 parts of dicyclopentadiene acrylate (DCPA), 25 parts of dicyclopentadiene oxyethyl acrylate (DCPEA), 10 parts of lauric acid acrylate (LA), 5 parts of 1,6-hexanediol diacrylate (HDDA), 13 parts of polyurethane acrylate resin, 3 parts of compound A, 1.8 parts of phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 1.0 part of silicone wetting agent, 0.3 parts of non-silicone foam breaking polymer defoaming agent, and 0.9 parts of ink blue pigment.

[0043] The preparation process is as follows: 15.9 parts of polyurethane acrylic resin are added into a stirred kettle, heated to 50°C, stirred for 10 minutes, and then 10 parts of tricyclodecane dimethanol diacrylate (TCDDA), 30.3 parts of dicyclopentadiene acrylate (DCPA), 25 parts of dicyclopentadiene oxyethyl acrylate (DCPEA), and compound A are added. 3 parts of lauric acid acrylate (LA) and 10 parts of the mixture were slowly added to the stirring kettle within 30 minutes. After the addition was completed, the temperature was lowered to room temperature. Then, 2.5 parts of 1,6-hexanediol diacrylate (HDDA), 1.8 parts of phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 0.3 parts of silicone wetting agent, and 0.3 parts of non-silicone foam breaking polymer defoamer were slowly added to the stirring kettle within 30 minutes. After the addition was completed, stir for 10 minutes. 2.5 parts of 1,6-hexanediol diacrylate (HDDA) and 0.9 parts of ink blue pigment were slowly added to the stirring kettle within 10 minutes. After the addition was completed, vacuum was evacuated to a vacuum degree of not less than -0.8 bar and stirred for 30 minutes. The coating preparation was completed. The stirring speed was controlled at 300rpm during the entire preparation process.

[0044] Example 3

[0045] This embodiment 3 provides a high-toughness photocurable coating, which is composed of the following components in parts by weight:

[0046] 10 parts of tricyclodecane dimethanol diacrylate (TCDDA), 30 parts of dicyclopentadiene acrylate (DCPA), 21 parts of dicyclopentadiene oxyethyl acrylate (DCPEA), 10 parts of lauric acid acrylate (LA), 5 parts of 1,6-hexanediol diacrylate (HDDA), 16 parts of polyurethane acrylate resin, 5 parts of compound A, 1.8 parts of phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 0.3 parts of silicone wetting agent, 0.3 parts of non-silicone foam breaking polymer defoaming agent, and 0.6 parts of ink blue pigment.

[0047] The entire preparation process is the same as that of Example 2. The order of adding materials is to first add the polyurethane acrylic resin, then add the acrylic monomer and the mixture of compound A, then add the acrylic monomer, the curing agent and the auxiliary agent mixture, and finally add the acrylic monomer and the pigment mixture.

[0048] Example 4

[0049] This embodiment 4 provides a high-toughness photocurable coating, which is composed of the following components in parts by weight:

[0050] 10 parts of tricyclodecane dimethanol diacrylate (TCDDA), 30 parts of dicyclopentadiene acrylate (DCPA), 22 parts of dicyclopentadiene oxyethyl acrylate (DCPEA), 10 parts of lauric acid acrylate (LA), 4 parts of 1,6-hexanediol diacrylate (HDDA), 13 parts of polyurethane acrylate resin, 8 parts of compound A, 1.8 parts of phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 0.3 parts of silicone wetting agent, 0.3 parts of non-silicone foam breaking polymer defoaming agent, and 0.6 parts of ink blue pigment.

[0051] The entire preparation process is the same as that of Example 2. The order of adding materials is to first add the polyurethane acrylic resin, then add the acrylic monomer and the mixture of compound A, then add the acrylic monomer, the curing agent and the auxiliary agent mixture, and finally add the acrylic monomer and the pigment mixture.

[0052] Comparative Example 1

[0053] 10 parts of tricyclodecane dimethanol diacrylate (TCDDA), 30 parts of dicyclopentadiene acrylate (DCPA), 25 parts of dicyclopentadieneoxyethyl acrylate (DCPEA), 10 parts of LA (dodecyl acrylate), 5 parts of 1,6-hexanediol diacrylate (HDDA), 13 parts of polyurethane acrylate resin, 1.8 parts of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 3 parts of vinyl trimethoxy silane, 1.0 parts of silicone wetting agent, 0.3 parts of non-silicone foam breaking polymer defoamer, and 0.9 parts of ink blue pigment.

[0054] The entire preparation process is the same as that of Example 2. The order of adding materials is to first add the polyurethane acrylic resin, then add the acrylic monomer mixture, then add the acrylic monomer, curing agent and auxiliary agent mixture, and finally add the acrylic monomer and pigment mixture.

[0055] Comparative Example 2

[0056] 10 parts of tricyclodecane dimethanol diacrylate (TCDDA), 30 parts of dicyclopentadiene acrylate (DCPA), 25 parts of dicyclopentadiene oxyethyl acrylate (DCPEA), 10 parts of LA (dodecyl acrylate), 5 parts of 1,6-hexanediol diacrylate (HDDA), 13 parts of polyurethane acrylate resin, 1.8 parts of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 3 parts of vinyl phosphonic acid, 1.0 part of silicone wetting agent, 0.3 parts of non-silicone foam breaking polymer defoamer, and 0.9 parts of ink blue pigment.

[0057] The entire preparation process is the same as that of Example 2. The order of adding materials is to first add the polyurethane acrylic resin, then add the acrylic monomer mixture, then add the acrylic monomer, curing agent and auxiliary agent mixture, and finally add the acrylic monomer and pigment mixture.

[0058] The high-toughness photocurable coatings obtained in Examples 2 to 4 of the present invention and Comparative Examples 1 to 2 were subjected to performance tests, mainly including shear strength test, adhesion test, insulation withstand voltage test, and bending resistance test. The results are shown in Table 1 below.

[0059] Among them, the specific method of shear strength test refers to GB / T 7124-2008 Determination of shear strength of adhesives (rigid material to rigid material) standard, and the bonding of the cured coating uses a commercially available structural adhesive with a shear strength greater than 20MPa. The specific method of adhesion test refers to GBT9286-1998 Scratch test of paint and varnish film. The specific method of insulation withstand voltage test refers to GB / T 1408.1-2016 Solid insulation material electrical strength test method; insulation internal resistance: DC1500V60s insulation internal resistance ≥500MΩ, withstand voltage: DC6000V 60s leakage current ≤0.1mA. The specific method of bending resistance test: install a φ32mm shaft rod on the cylindrical shaft bending tester, place the tester firmly and insert the test piece, so that the coating to be tested faces the shaft rod, is in a vertical position with the shaft rod, and contacts the shaft rod; operate the instrument to bend the test piece 180° at a stable speed within 1 to 2 seconds; restore the instrument, take out the test piece and check the appearance of the coating under sufficient light. The preparation process of the sample is as follows: use laser processing to test the aluminum plate of the required size, and the roughness Rz of the aluminum plate after processing is required to be not less than 8, and then apply the light-curing coating on the surface of the aluminum plate by spraying or printing. The coating thickness is 100-120 microns, and it is cured by electrodeless lamp, and the curing energy is not less than 6000mj / cm 2 .

[0060] Table 1 Test results

[0061]

[0062] It can be seen from the above that the photocurable coating of the present invention significantly improves the shear strength and adhesion performance, and improves the bending crack resistance performance while meeting the insulation withstand voltage requirements.

[0063] In this specification, the present invention has been described with reference to specific embodiments thereof. However, it is apparent that various modifications and variations may be made without departing from the spirit and scope of the present invention. Therefore, the description should be regarded as illustrative rather than restrictive.

Claims

1. A high-toughness photocurable coating, It is characterized in that In parts by weight, it includes the following components: 60-85 parts of acrylate monomer; 8-25 parts of polyurethane acrylate resin; Compound A 2-8 parts; 1 to 5 parts of photoinitiator; Wetting agent 0.1-0.8 parts; Defoaming agent 0.1-0.8 parts; Pigment 0.5-2 parts; The preparation method of compound A comprises the following steps: (1) Compound B is added to toluene, and after azeotropic dehydration under nitrogen, the mixture is cooled to 80°C to 100°C, chloroplatinic acid is added, and a mixture of compound C and toluene is added dropwise, and the mixture is stirred for reaction to obtain compound D; Wherein, the structural formula of compound B is: ; The structural formula of compound C is: ; The structural formula of compound D is: , where n=10~30; (2) Compound D is added to toluene, and concentrated sulfuric acid is added, the temperature is raised and acrylic acid is added. After the reaction is completed, an intermediate E is obtained. The temperature is lowered to 100° C. to 120° C., and a mixed solution of dibenzoyl peroxide, vinylphosphonic acid and toluene is continuously added to the reaction solution. After the reaction, toluene is distilled off under reduced pressure to obtain the compound A. The structural formula of the intermediate E is: , where n=10~30.

2. The high-toughness photocurable coating according to claim 1, It is characterized in that The polyurethane acrylate resin is selected from one or both of aliphatic polyurethane acrylate resin and aromatic polyurethane acrylate resin, and has a resin viscosity of 10,000 to 80,000 cps@60°C, an elongation of 20 to 150%, and a functionality of 2 to 6.

3. The high-toughness photocurable coating according to claim 1, It is characterized in that The acrylic acid ester monomers include: 5 to 20 parts of a first acrylic acid ester monomer, 10 to 40 parts of a second acrylic acid ester monomer, 10 to 40 parts of a third acrylic acid ester monomer, 3 to 20 parts of a fourth acrylic acid ester monomer, and 3 to 10 parts of a fifth acrylic acid ester monomer; The first acrylate monomer is selected from one or both of tricyclodecane dimethanol diacrylate and ethoxylated trimethylolpropane trimethacrylate; The second acrylate monomer is selected from one or two of dicyclopentadiene acrylate, cyclotrimethylolpropane formal acrylate, isobornyl methacrylate and isobornyl acrylate; The third acrylate monomer is selected from one or two of dicyclopentenyl ethoxylated acrylate, dicyclopentenyl ethoxylated methacrylate and dicyclopentyl methacrylate; The fourth acrylate monomer is selected from one or two of lauric acid acrylate, octadecyl to docosyl acrylate, lauric acid methacrylate and 2-ethylhexyl methacrylate; The fifth acrylate monomer is selected from one or two of 1,6-hexanediol diacrylate, ethoxylated 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, neopentyl glycol diacrylate, propoxylated neopentyl glycol diacrylate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate and diethylene glycol dimethacrylate.

4. The high-toughness photocurable coating according to claim 1, It is characterized in that The acrylate monomers are composed of tricyclodecane dimethanol diacrylate, dicyclopentadiene acrylate, dicyclopentenyl ethoxylated acrylate, lauric acid acrylate and 1,6-hexanediol diacrylate.

5. The high-toughness photocurable coating according to claim 1, It is characterized in that The photoinitiator is selected from α-cleavage free radical photoinitiator or hydrogen elimination free radical photoinitiator.

6. The high-toughness photocurable coating according to claim 1, It is characterized in that The photoinitiator is selected from acylphosphine oxides.

7. The high-toughness photocurable coating according to claim 1, It is characterized in that The wetting agent is an organosilicon wetting agent, and the defoaming agent is a foam-breaking polymer mixture that does not contain organosilicon.

8. The high-toughness photocurable coating according to claim 1, It is characterized in that The pigment is ink blue.